Lipoxygenase regulation in vivo and in vitro by lipid compounds - Skaterna, T.D.; Kopich, V.M.; Kharitonenko, G.I.; Kharchenko, O.V. (Вiopolymers and Cell, 2015)
Lipoxygenases (LOs) are known as one of the enzymes of lipid peroxidation. The majority of LOs are soluble enzymes and have affinity to membranes. The enzyme translocation from a cytosol to a membrane surface is one of the stages of regulation of the amount of LO catalysis products in the cell. A sorption to the membrane surface is described for most LOs from plant and animal sources. This review presents the data about regulation of the LO activity by the lipid compounds – both natural and chemically modified. Lipids might regulate the LO activity through: protein-lipid interactions of C2 domain with the membrane, changes in the enzyme affinity, the LOs translocation, allosteric regulation, increase in the selectivity towards substrates. The regulatory effect of active compound on the enzyme activity depends on the lipophilicity of effectors. Considering the LO activity it is necessary to take into account the enzyme microenvironment and its influence on the range of the LO products. Ліпоксигенази (ЛО) відомі як одні з ферментів перекисного окислення ліпідів. Більшість ЛО є розчинними ферментами та характеризуються аффіністю до мембран. Транслокація ферменту з цитозолю на мембранну поверхню одна з стадій регуляції рівня продуктів ліпоксигеназного каталізу у клітині. Сорбція на мембранну поверхню описана для більшості ЛОз з рослинних та тваринних джерел. Даний огляд представляє дані по регуляції ЛОз активності природніми та хімічно модифікованими речовинами ліпідної природи. Здатність ліпідів регулювати ЛО активність може здійснюватись через: білок-ліпідні взаємодії C2 домену з мембраною, зміну аффінності ферменту, транслокацію ЛОз, алостеричну регуляцію, збільшення селективності до субстрату. Регуляторний вплив активної сполуки на ферментативну активність залежить від рівня ліпофільності ефекторів. При поясненні ліпоксигеназного каталізу необхідно враховувати вплив мікрооточення ферменту на рівень ЛО. Липоксигеназы (ЛО) известны как одни из ферментов перекисного окисления липидов. Большинство ЛО растворимые ферменты и характеризуются аффиностью к мембранам. Транслокация фермента из цитозоля на мембранную поверхность одна из стадий регуляции уровня продуктов липоксигеназного катализа в клетке. Сорбция на мембранную поверхность описана для большинства ЛОз из растительных и животных источников. Данный обзор представляет данные по регуляции ЛО активности природными и химически модифицированными соединениями липидной природы. Возможность липидов регулировать ЛО активность может осуществляться через: белок-липидные взаимодействия C2 домена с мембраной, изменение аффинности фермента, транслокацию ЛОз, аллостерическую регуляцию, селективность к типу субстрата. Регуляторное влияние активного соединения на ферментативную активность зависит от уровня липофильности еффекторов. При объяснении липоксигеназного катализа необходимо учитывать влияние микроокружения фермента на уровень ЛО продуктов.